A simple procedure for optimising the polymerase chain reaction (PCR) using modified Taguchi methods. - Cobb, B D (1994)
Taguchi methods are used widely as the basis for development trials during industrial process design. Here, we describe their suitability for optimisation of the PCR. Unlike conventional strategies, these arrays revealed the effects and interactions of specific reaction components simultaneously using just a few reactions, negating the need for extensive experimental investigation. Reaction components which effected product yield were easily determined. In addition, this technique was applied to the qualitative investigation of RAPD-PCR profiles, where optimisation of the size and distribution of a number of products was determined.